The Republic of Turkey, From An Islamic Caliphate To A Nation State - Abu Bakar (Fakultas Syariah (Syari'ah Faculty ), 2018)
Ottoman Caliphate in Istanbul was the last empire based on Islamic caliphate system. It ruled some regions in Asia, Africa and Europe. Islam as a supra identify was able to unite nations under the flag of Islamic caliphate. The decline of Ottoman caliphate was inevitable as the effect of social development and international political dynamics that led to the caliphate’s engagement in World War I. Islamic caliphate was considered fail to save the empire that led to immerging idea of nationalism in order to recover ottoman people who lost the battle. The nationalism of Turkey was ruled by military that latter turned into Nation State of The Republic of Turkey. Therefore, the idea of Islamic caliphate must be diminished and replaced by secularism. This led to the conflict between Islamists and nationalists, and eventually nation state of turkey managed to get rid of Islamic caliphate system.